Re-assessing value (co)-creation and cooperative advantage in international networks - Butler, Bella; Batt, Peter (Elsevier Inc., 2014)
From the Fifth Meeting of the IMP Group in Asia, the ten papers selected for this special edition have been grouped under four broad themes: network evolution and performance; networks in emerging contexts' value (co)creation; and network structure, position and performance. Not unexpectedly, many of the themes overlap, reflecting both the complexity and diversity of network theory.